Ruta gastronómica en Municipios aledaños a Cúcuta (2021)
The proposal for a design of a gastronomic route to municipalities surrounding the city of Cúcuta, is carried out to enhance the typical gastronomy of the department of Norte de Santander. Through a study that was carried out with surveys and investigations for the selection of the municipalities that will make part of the route. It should be noted that tourist places will also be included in the itinerary so that the tourist can learn about the North Santandereana culture.